Position control for planar four-link underactuated manipulator with a passive third joint. (April 2019) - Liu, Dong; Lai, Xuzhi; Wang, Yawu; Wan, Xiongbo; Wu, Min
Abstract: This paper presents a position control strategy based on the differential evolution (DE) algorithm for a planar four-link underactuated manipulator (PFUM) with a passive third joint, which is to move its end-point from any initial position to any target position. Based on the structural characteristic of the PFUM, a model reduction method is conceived to reduce the PFUM to a planar virtual three-link manipulator and a planar Acrobot in turn. Considering the existence of the angle constraint in the planar Acrobot, the DE algorithm is used to optimize and coordinate the control objective of each reduced system, and also to ensure the target angles of the planar Acrobot corresponding to the target position of the PFUM can be found. Simulations demonstrate the validity of the proposed control strategy. Highlights: The position control of the planar four-link underactuated manipulator is achieved. An effective model reduction strategy is proposed. The DE algorithm is used to optimize the control objective of each reduced system.